MONITORING OF THE INOPERATIVE ENVISAT SATELLITE’S BEHAVIOUR - Shakun, L.; Koshkin, N.; Korobeynikova, E.; Melikynts, S.; Strakhova, S.; Terpan, S. (Одеські астрономічні публікації, 2013)
New positions data and light curves were received for the inoperative Envisat spacecraft still in orbit. The satellite pole and sidereal rotation period were determined on the base of the photometric data for the period from April to August 2013. The presence of a precession of the Envisat rotation axis was deduced.